Linguistics Specificity of Universities Prospectuses: A Corpus-Based Genre Analysis - Aiman Qaiser; Syed Shujaat Ali; Naveed-Ur-Rehman Khattak (Corporum)
This study investigates the specific lexical choices found in university prospectuses while examining the linguistic structures that define their textual characteristics and determining the genre type by comparing it with similar text types to understand the unique language features of these documents. The necessary prospectuses were downloaded from the universities' online platforms to achieve this objective. A collection of text samples was assembled by examining various sections of university websites to create a representative corpus. The section titled Introduction, About Us, Vice Chancellor Messages, Vision, Mission, and Facilities. A quantitative approach was employed; lexical and linguistic features were quantified to compare with registers' specific dimensions scores as studied in Biber,and for framing the textual dimensions. Functions of lexical specificity were interpreted to describe the workings of tools of lexicalspecificity. The data was analyzed with the help of software like MAT and AntConc. The investigation of the data utilized theoretical frameworks, including Hyland's (2009) specificity model alongside Biber's (1993) multidimensional analysis model. The research indicates that university prospectuses frequently employ lexical items that predominantly include self-reference terms, hedging expressions, directional words, reporting verbs, and lexical bundles. Through Biber's (1993) multidimensional analysis, the research findings indicate that university prospectuses align most closely with the learned exposition text type, encompassing registers such as official documents, press reports, and academic prose, thus establishing it as a distinct genre.